TAHAP PERKEMBANGAN MORAL ANAK PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Miftahul Jannah (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2022)
This study discusses the stages of children's moral development in the perspective of and Islamic psychological education. The topics discussed in this study including the definition of morals according to experts, the stages of children's moral development, and what factors influence children's moral development. This study uses a qualitative approach, and literature study by taking data sources from books and several journals on the internet related to the stage of moral development of children from the perspective of Islamic education psychology. The results of the study are: in Islamic psychological education, education is not merely about increasing children's intellectuality and skills, but more importantly, it aims to develop moral values in children. Therefore, children are expected to have good morals and can reflect moral values as well as human values, so that children can respect themselves as well as respect other people, whether in terms of physical, opinion and differences in race, ethnicity, and religion.Keywords : Psychological Study, moral Development, Islamic psychological Perspective.